Формування стійкості потенціалу беззбиткового розвитку сільськогосподарських підприємств - Булкін, Сергій Сергійович; Bulkin, S. (Дніпровський ДАЕУ, 2021)
Досліджено теоретико-методичні та практичні аспекти реалізації організаційно-економічного інструментарію формування стійкості потенціалу беззбиткового розвитку сільськогосподарських підприємств. Удосконалено понятійно-категоріальний апарат у частині уточнення сутності економічних категорій «стійкість», «беззбитковий розвиток», «стійкість потенціалу беззбиткового розвитку сільськогосподарських підприємств». Здійснено комплексну оцінку впливу системно-ресурсної компоненти на стійкість беззбиткового розвитку сільськогосподарських підприємств та виявлено чинники, що впливають на її формування. Розроблено теоретико-методичні засади дослідження процесу формування стійкості потенціалу беззбиткового розвитку сільськогосподарських підприємств. Удосконалено аналітико-математичний інструментарій діагностики стійкості потенціалу беззбиткового розвитку сільськогосподарських підприємств, який доповнено використанням експертного оцінювання цільових параметрів самофінансування, факторним аналізом визначення їх вагомості та кластерним аналізом діапазону граничних меж впливу. Розроблено методичний підхід до планування в системі формування стійкості потенціалу беззбиткового розвитку сільськогосподарських підприємств з використанням інструментарію операційного аналізу прогнозних параметрів зміни обсягу та ціни реалізації сільськогосподарської продукції, а також рівня змінних та постійних витрат виробництва. Надано пропозиції щодо підвищення рівня стійкість потенціалу беззбиткового розвитку сільськогосподарських підприємств із урахуванням інформаційного забезпечення технологічних процесів їх виробничої діяльності. The dissertation is devoted to scientific and practical issues of formation of stability of potential of unprofitable development of agricultural enterprises. The study of the modern paradigm of the theory of sustainability of enterprise development revealed the content of the category "sustainability of the potential of break-even development of agricultural enterprises" as a set of components of the business system of agricultural enterprises (production, marketing, investment and financial). They provide the ability to return to a break-even state of development through the implementation of mechanisms of economic relations for the formation and use of production resources in a dynamic environment. Ensuring the reproductive process stability potential cost recovery of agricultural enterprises in its essence is dynamically cyclical. It argued that an important task of today's economy is to form the stability of the potential for break-even development of agricultural enterprises in the conditions of occurrence and impact of destabilization processes and crises. Stability, as an internal property of the economic system, is expressed by the ability of the enterprise to withstand fluctuations caused by changes in the external and internal business environment and to carry out effective activities to achieve its own development goals. Sustainability of break-even development potential characterizes the opportunities to attract resources to finance strategic areas of business development. From the standpoint of systems theory and concepts of self-organization, the stability of the enterprise as a business system, involves qualitative changes in its potential and the reproductive process of production and economic activity. The study of theoretical provisions of the sustainability of the potential of break-even development of agricultural enterprises allowed to identify its system-resource component (cash, financial investments, receivables, highly liquid products), which can provide a reproductive process of the production cycle and competitive advantages of economic entities in the short term. Isolation of qualitative features of the system-resource component of the formation of the stability of the potential of breakeven development allows to identify them among the set of tools of the economic system, to determine individual forms of manifestation and causal relationships. It is established that the current state of functioning of agricultural enterprises of Dnipro region is characterized by instability and a significant degree of risk of management in a changing environment, which has a significant impact on the efficiency of their economic activity. According to the results of the method of assessment of the main components and taxonomic analysis, a close correlation was established between the indicators of the three spheres of the economic process of agricultural enterprises: resource provision, production and sales. The analysis of resource provision of agricultural enterprises showed that increasing the efficiency of the resource component of the sustainability potential of the break-even development of agricultural enterprises is achieved with the optimal ratio of various elements of current assets in the production and financial cycle. The share of enterprises in Solonyansky district with an average level of resource provision in the structure of current assets is almost constant. A significant reduction in resource supply current assets in the area due to a decrease in profitability. It is established that the sustainability of agricultural enterprises is determined by the presence of potential reserves, the use of which is impossible without self-financing the break-even development of economic entities. Since the process of self-financing of economic activity is characterized by the financial independence of the enterprise, the availability of equity to cover current liabilities and sources of self-sufficiency of break-even development, all target parameters of self-financing must be high. According to the results of clustering of agricultural enterprises of Solonyansky district, the ranges of limits of influence of target parameters of self-financing on the level of stability of potential of their break-even development are identified. Calculations show that 10,7% of agricultural enterprises in the district are in a high range of target parameters of self-financing, 21,4% of enterprises – in the middle range, 42,9% – in the low range and 25,0% – in the critical range. We believe that the formation of strategic priorities to increase the sustainability of the potential of break-even development of agricultural enterprises should be based on a program-targeted approach to the reproduction of stable economic growth in the choice of tools to regulate the resource provision of agricultural production. Developed integral indicator methodical approach to planning in the system of cost recovery potential sustainability of agricultural enterprises, which unlike common, involves the use of predictive analysis tools operating parameters of volume and price changes of agricultural products and of variable and fixed costs. In order to improve the stability of potential cost recovery of agricultural enterprises proposed introduction of information technologies at all levels of resource components of the reproductive cycle of agricultural production using modern telematics systems.
Formation of stability of potential of unprofitable development of agricultural enterprises
Keywords: економічна стабільність; economic stability; бізнес-система; business system; управління; management; сільськогосподарське підприємство; agricultural enterprise; розвиток; development